E-commerce customers behavior research using cohort analysis: A case study of COVID-19 - Solomiia Fedushko; Taras Ustyianovych (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Cohort analysis is a new practical method for e-commerce customers' research, trends in their behavior, and experience during the COVID-19 crisis. The purpose of the research is to validate the efficiency of this method on the e-commerce records data set and find out the critical factors associated with customer awareness and loyalty levels. The cohort analysis features engineering, descriptive statistics, and exploratory data analysis are the main methods used to reach the study purpose. The research results showed that cohort analysis could answer various business questions and successfully solve real-world problems in e-commerce customer research. It could be extended to analyze user satisfaction with a platform's technical performance and used for infrastructure monitoring. Obtained insights on e-commerce customers' awareness and loyalty levels show the likeliness of a user to make a purchase or interact with the platform. Key e-business aspects from a customer point of view are analyzed and augment the user-experience understanding to strengthen customers' relationships in e-commerce.
Keywords: 650; business informatics; cohort analysis; COVID-19; customers research; digitalization; e-business; e-commerce; open innovations